2018
DOI: 10.1371/journal.pone.0192400
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinographic evidence suggesting that the type 2 diabetic retinopathy of the sand rat Psammomys obesus is comparable to that of humans

Abstract: PurposeType 2 diabetic retinopathy is the main cause of acquired blindness in adults. The aim of this work was to examine the retinal function of the sand rat Psammomys obesus as an animal model of diet-induced type 2 diabetes when subjected to a hypercaloric regimen.Materials and methodsHyperglycemia was induced in Psammomys obesus by high caloric diet (4 kcal/g). The visual function of control (n = 7) and diabetic (n = 7) adult rodents were followed up during 28 consecutive weeks with full-field electroretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In a previous manuscript (Dellaa et al, 2018), we reported ERG findings in P . obesus that had been affected with diabetes for 7 months.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…In a previous manuscript (Dellaa et al, 2018), we reported ERG findings in P . obesus that had been affected with diabetes for 7 months.…”
Section: Introductionmentioning
confidence: 64%
“…In contrast (Kohzaki et al, 2008), showed unaffected b‐waves 11 weeks after STZ injection in Sprague–Dawley rats. No difference was detected in the photopic b/a‐wave ratio during 6 months of the experiment in P. obesus , this fact shows that a‐ and b‐waves are similarly decreased (Dellaa et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations